Novel DDX41 variants in Thai patients with myeloid neoplasms - Chantana Polprasert (2020)
© 2019, Japanese Society of Hematology. Germline DDX41 mutations were recently reported to cause MDS/AML and donor-derived leukemia after transplantation. While previously described in Western countries, DDX41 variants have not been reported in a Southeast Asian population. We performed targeted sequencing of blood or bone marrow samples from 109 Thai patients with myeloid malignancies. Among the 109 patients (75 MDS, 8 MPN, 11 MDS/MPN and 15 AML), the most frequent mutations were in ASXL1 (17.4%), TET2 (16.5%) and SRSF2 (12.8%), respectively. DDX41 variants were detectable in six (5.5%) cases. Four patients exhibited three presumable germline DDX41 mutations: p.S21fs (n = 2), p.F235fs (n = 1), and p.R339H (n = 1). While p.S21fs was previously reported in myeloid neoplasm, the latter two variants have not been described. Two of these cases harbored concomitant probable germline/somatic DDX41 mutations (p.S21fs/p.R525H and p.R339H/p.K494T), while the other two patients carried only somatic mutations (p.R525H and p.F438L). The p.K494T and p.F438L variants have not been previously reported. In patients with DDX41 alterations, the diagnoses were MDS with excess blasts (4), secondary AML (1) and low-risk MDS (1). In conclusion, we identified DDX41 variants in Thai patients with myeloid malignancies in which these variants could be used to assess predisposition to MDS in Southeast Asia.